Improving Studentsâ Writing Paragraph Ability by Using Praise- Question- Polish Method - Aruan, Rumiri (Proceedings of the UR International Conference on Educational Sciences, 2018)
This learning improvement research seeks to improve the learning process of writing by applying Praise Question Polish ( PQP ) method . Thesubject of the research is the second semester of the academic year students of 2017/2018. Before applying this method,the writer conducted a pre - test . The result of the pre - test showed that the studentsâ paragraph writing skills is low. If it is converted to the Universitys academic regulations of Riau, only 5.4 % of students got good score, 32.4 % got average score, 48.6 % of students got less score, and 13.5 % were failed category. After the application of the Praise Question Polish conducted in two cycles, the second cycle results showed the significant changes. The percentage of students scores in cycle 2 showed that 2.7% got excellent, 48.6 % got good score, 29,7% got average score, 10,8 % got less score, and 5.4 % were failed category. The significant increase is also seen in all of the elements of paragaph writing such as Format, Mechanics, Content, Organization and Grammar . From the results above could be concluded that the application of PQP is very recomended in teaching writing paragraph.